2018
DOI: 10.1002/ange.201808049
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Thermal Atomization To Convert Supported Nickel Nanoparticles into Surface‐Bound Nickel Single‐Atom Catalysts

Abstract: The arrangement of the active sites on the surface of ac atalysts can reduce the problem of mass transfer and enhance the atom economy.H erein, supported Ni metal nanoparticles can be transformed to thermal stable Ni single atoms,mostly located on the surface of the support. Assisted by N-doped carbon with abundant defects,t his synthetic process not only transform the nanoparticles to single atoms,b ut also creates numerous pores to facilitate the contact of dissolved CO 2 and single Ni sites.The proposed mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Nickel is able to form single Ni atoms (cations) on the surface of nitrogen-doped carbon [16], which could be the active sites for some hydrogenation [17] and CO 2 electroreduction [18][19][20][21] reactions. It is not known whether these Ni species can be active in the formic acid decomposition reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel is able to form single Ni atoms (cations) on the surface of nitrogen-doped carbon [16], which could be the active sites for some hydrogenation [17] and CO 2 electroreduction [18][19][20][21] reactions. It is not known whether these Ni species can be active in the formic acid decomposition reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, we synthesized Ni SACs that anchored on the edges of a porous carbon structures with and without the N dopant, and found that the Ni SACs without N doping show a very small current for CO 2 RR with selectivity less than 10%, while the Ni SACs coordinated with N show a high current density for CO 2 RR with selectivity over 90% . Yang et al found that the strong coordination of Ni with N could split Ni atoms from Ni NPs and the continuous loss of atomic Ni species from the NPs would finally result in atomization of Ni NPs . These findings further demonstrate that the atomically dispersed Ni atoms are most likely coordinated with N rather than C. The results so far show that the Ni atoms that coordinated with N could be the major active center for CO 2 RR.…”
Section: Electrochemical Co2 Conversion On Single‐atom Catalystsmentioning
confidence: 91%
“…The variable metal nodes and organic linkers enable the post‐modification and more possible synthetic routes. The ZIF‐8 MOF is a frequent choice as the SAC precursor due to the above reasons, and the SACs derived from it have been reported to exhibit excellent CO 2 RR performance 113,142,149‐154 …”
Section: Electrochemical Application Of Single Atom Catalystsmentioning
confidence: 99%